“¡Vivan las cadenas! A people who wanted to remain under oppression?” An experience of historical perspective-taking - Paricio Royo, Javier; Guillén Franco, Marcos (Clio. History and History Teaching, 2020)
The materials are offered for a historical empathy experience for 4th ESO, in which students must construct an explanation for the apparent absolutist position of a large part of the Spanish people with the return of Ferdinand VII in 1814. Using primary sources, both texts and images, students explore different aspects of the circumstances, ideas and interests that converged in those events and which will constitute the raw material for their historical reasoning